Speech Act In Joe Biden Speech “Build Back Better World” At UN General Assembly - M. Nur Efendi; Sudirman Maca; Andi Tenri Abeng (Fakultas Sastra, Universitas Bosowa, 2022)
This research discussed about President Joe Biden Speech Act at UN General Assembly on September 21, 2021 which aimed to find out the kinds of communication function in illocutionary act and to identify the perlocutionary act effect contained in the speech. This research use John Searle theory about classification of illocutionary act and John L. Austin theory about perlocutionary act. Then, the data were analyzed using descriptive-qualitative method. The writer used speech transcript as the instrument to find out the valid data. There were five of kinds communication function in illocutionary act that President Joe Biden used in his speech which were, assertives (giving information, remaining, assure, and statement), directives (suggesting, and requesting), commissives (promising, offering, and pledge), expressives (express his feelings), and declaratives (declare that United State has stop with war). The writer also found 4 perlocutionary act effects and responses from the audience, which were; pandemic Covid-19 donation, American government ended conflict in Afghanistan, the responses of United State government to the climate crisis, and American government will continue to be the largest contributor to humanitarian assistance.